A predictive control approach for bidirectional DC-DC power converter in supercapacitor energy storage systems - Anh, Pham Tuan; Chuong, Nguyen Van; Duc, Cao Xuan; Quang, Nguyen Phung (Journal of Computer Science and Cybernetics, 2015)
A possible solution to mitigate the wind power fluctuations is integrated energy storage systems (ESS) to the wind energy conversion systems (WECS). The supercapacitor ESS (SCESS) is able to smooth out the output power of wind turbine by exchanging bidirectional power between wind turbine and supercapacitor through power conversion system. The SCESS consists of supercapacitor, serving as a DC power source, and power conversion system comprising a bidirectional DC-DC converter and a bidirectional DC-AC converter. Although control methods for a DC-AC converter are almost fully developed, there is not any scientific research for nonlinear control design of DC-DC converter due to the shortage of its nonlinear model describing power exchange process. This paper focuses on a SCESS in terms of modeling and control designing aim to manage active power flow between the grid and the SCESS. A predictive control algorithm for discrete-time bilinear state-space model of a non-isolated bidirectional DC-DC converter is proposed. This algorithm is supplementary methods for this converter besides linear or hysteresis control methods in other research. Simulations validate the effectiveness of the proposed control.